Translation and validation of Taiwanese version of the Early Childhood Oral Health Impact Scale (ECOHIS) - Ming-Hsuan Sheen; Szu-Yu Hsiao; Shun-Te Huang (Elsevier, 2020)
Background/purpose: Treating and preventing dental caries in children have been major health concerns in Taiwan. However, little discussion on oral health-related quality of life in Taiwanese preschooler exists. This study aimed to construct and validate a Taiwanese version of the Early Childhood Oral Health Impact Scale (ECOHIS) for preschool children in Taiwan. Materials and methods: A Taiwanese version of the ECOHIS was developed using the forward-backward translation method. Our study population (n = 251) comprised children aged 3-6 years old. Parents of the children signed informed consent and self-completed ECOHIS. Data were analyzed for internal reliability using Cronbach's alpha coefficient, and item-to-total correlation was determined. Criterion validity was tested for the relationship between ECOHIS scores and caries experience (dmft). A multiple linear regression model was used to assess the independent variables of the ECOHIS. Results: Cronbach's alpha for the total score of the Taiwanese version of ECOHIS was 0.76. The validity of the ECOHIS was tested, and scores of both the total scale and family impact section were found to be statistically significantly related to dmft (P < 0.005). Multiple linear regression analysis revealed that with an increase in dmft, the total score of the ECOHIS significantly increased (95% CI = 0.22-0.63, P < 0.001). Conclusion: The Taiwanese version of the ECOHIS is a valid and reliable tool to assess the oral health-related effect on 3- to 6-year-old children in Taiwan.